Customer Relationship Management (CRM) Strategy in Increasing Consumer Loyality - Ni Nyoman Suarniki; Ibrahim Daud (PT. Anagata Sembagi Education, 2024)
This research investigates the impact of Customer Relationship Management (CRM) strategies on consumer loyalty in the context of businesses implementing CRM practices. The purpose of this study is to examine how CRM strategies, such as customer identification, interaction, and personalization, influence consumer satisfaction and loyalty. Using a quantitative research approach with a descriptive correlational design, the study surveyed 225 respondents through a questionnaire. The data were analyzed using multiple regression analysis to assess the relationship between CRM strategies and consumer loyalty. The results reveal that CRM strategies have a significant positive impact on consumer loyalty, with strong correlations and statistical significance. The findings suggest that businesses can enhance consumer loyalty by improving CRM practices, focusing on personalized services, leveraging customer data, and engaging with consumers through effective communication channels. The study also highlights the importance of maintaining long-term relationships with consumers through loyalty programs and personalized experiences. These findings offer valuable recommendations for businesses to strengthen customer retention, satisfaction, and loyalty. Furthermore, the research emphasizes the importance of continuous CRM adaptation to meet evolving consumer needs and technological advancements. This study provides a comprehensive understanding of how CRM strategies contribute to building a loyal consumer base and fostering long-term business growth.